Nanostructured Lipid Carrier-Based Hydrogel of Fenoprofen Calcium for Sustained Release: Optimization, Characterisation, and in vitro Evaluation - Zahoor, Ishrat; Sharma, Neelam; Singh, Sukhbir (Indian Journal of Pharmaceutical Education and Research, 2026)
Objectives: Fenoprofen Calcium (FEN) has short elimination half-life, frequent dosage administration and numerous gastrointestinal side effects on oral administration. The primary objective of this research was to synthesize optimized FEN-loaded Nanostructured Lipid Carriers (FEN-NLCs) using Box-Behnken design and develop its hydrogel with enhanced dissolution in conjunction with sustained drug release. Materials and Methods: FEN-NLCs were synthesized by solvent evaporation technique using Compritol 888 and oleic acid, optimised by Box-Behnken design and characterized by FTIR and HR-TEM. The FEN-NLC-hydrogel was evaluated for physicochemical characteristics and in vitro drug release study. Results: The desirability function of optimal formulation was found 0.874 with predicted values of 92.89 %w/w entrapment efficiency, 136.19 µg/cm2/hour flux and 72.98%w/w yield. FEN-NLC-hydrogel was developed which illustrated pseudo-plastic flow behavior. FEN-hydrogel, PM-hydrogel and Fen-NLC-hydrogel exhibited cumulative drug release of 19.5%, 20.79% and 30.42% within 4 hr; 44.57%, 47.37% and 79.86% within 8 hr while 45.6%, 47.81% and 93.34% in 24 hr which revealed 2-folds enhancement in drug dissolution. This indicated poor in vitro drug release from plain drug-hydrogel with negligible increase in drug release after 8 hr. While Fen-NLC-hydrogel showed sustained increase in drug release till 24 hr. The n-value for peppas model was 0.8676 which showed anomalous phenomenon and sustained drug release from FEN-NLCs. Conclusion: The current research conclusively manifested that Fenoprofen Calcium loaded nanostructured lipid carriers-based hydrogel holds great prospective for providing sustained drug release.
Keywords: Fenoprofen Calcium; Box-Behnken design; Nanostructured lipid carriers; Sustained; drug release